Passive acoustic monitoring of the bottlenose dolphin Tursiops truncatus to determine continuous presence in Ensenada de La Paz, Mexico - Gauger, Marco FW; Caraveo-Patiño, Javier; Romero-Vivas, Eduardo (Revista de Biología Marina y Oceanografía, 2021)
Bottlenose dolphins (Tursiops truncatus) are ecosystem sentinels. In the Gulf of California, Mexico, they are found in areas that overlap with human activities, as in the case of the Ensenada de La Paz lagoon. A custom-made recorder -moored at medium depth (2.0 m) in the entrance to the lagoon- recorded acoustic data from June to November 2017 (8 deployments; 293 h). Whistles -an indicative of bottlenose dolphin presences- were pooled over time to acquire acoustic encounters, which were analysed to infer continuity of animal presence and test for statistically significant differences between deployments, day and night, and hours. Whistles were recorded during all deployments and evidenced night-time presence of bottlenose dolphins in the lagoon. Significant differences of acoustic encounters were observed between ‘Jun-Jul’ and ‘Sep-Nov’. Acoustic encounters were higher at night but were not different at an hourly level. Acoustical data proved the continuous presence of bottlenose dolphins, highlighting the importance of the Ensenada de La Paz for their population. This initial study highlights the usefulness of long-term passive acoustic monitoring to inform stake holders involved in management and conservation plans.